What eye movements reveal about strategy encoding of words in younger and older adults. Issue 4 (20th April 2020) - Taconnat, Laurence; Morel, Shasha; Guerrero – Sastoque, Lina; Frasca, Mickaël; Vibert, Nicolas
ABSTRACT: The main goal of this study was to explore the organizational strategies used by younger and older adults when encoding words, using eye-tracking. Participants had to learn a set of organizable words and then a set of non-organizable words, each presented on a single display. Participants were then asked to recall the words of each set in the order in which they came to their mind. Hence, the participants' encoding strategies revealed by eye-tracking could be directly related to their subsequent memory performance. The results confirmed the detrimental impact of aging on memory and the weaker use of organizational strategies by older adults during the recall phase. The eye-tracking data showed that when they encode the words, older adults do not look at them for as long as younger adults, probably because of slower eye movements. They also revealed that compared to younger adults, older adults were much less able to adapt their word scanning strategy according to whether the words to encode were organizable or not. Finally, the relationships that were found between the recall scores and the eye-tracking data suggest that the eye movement pattern at learning can predict how people will recall the words.